2020
DOI: 10.1002/pon.5576
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence in childhood cancer survivors: A developmental perspective from infancy to young adulthood

Abstract: Aims: Fear of cancer recurrence (FCR) is among the most prevalent and distressing concerns reported by cancer survivors. While younger age is the most consistent predictor of elevated FCR, research to date has focused almost exclusively on adult cancer survivors. This is despite the fact that children with cancer are more likely to survive compared to adults, and will become regular, lifelong users of the medical system to mitigate the effects of toxic treatment. The early experience of cancer yields unique ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
(96 reference statements)
2
20
0
Order By: Relevance
“…This stands in contrast with adult studies which have consistently reported greater fear of recurrence with declining age. Taken together, these findings suggest that those who experience cancer and/or who are survivors during adolescence and early adulthood may be a particularly vulnerable group for experiencing greater fear of recurrence 36 . There are likely multiple developmental reasons for this increased vulnerability, including a greater understanding than younger children about risk for recurrence, a perception of a longer future ahead than older adults, and age‐normative vulnerability for the development of anxiety and related mental health issues.…”
Section: Discussionmentioning
confidence: 90%
“…This stands in contrast with adult studies which have consistently reported greater fear of recurrence with declining age. Taken together, these findings suggest that those who experience cancer and/or who are survivors during adolescence and early adulthood may be a particularly vulnerable group for experiencing greater fear of recurrence 36 . There are likely multiple developmental reasons for this increased vulnerability, including a greater understanding than younger children about risk for recurrence, a perception of a longer future ahead than older adults, and age‐normative vulnerability for the development of anxiety and related mental health issues.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the impact of interventions on caregivers' FCR remains unclear. We excluded studies of caregivers of children/adolescents with cancer, as their distinctive caregiver-care recipient relationship dynamic may differentially impact FCR [104]. Many studies focused on male caregivers of women with breast cancer, potentially limiting the generalisability of results to other caregiver populations.…”
Section: Review Limitationsmentioning
confidence: 99%
“…However, based on our clinical assessment using the K‐SADS, we found that rates of anxiety disorders remain high, with 26.9% of our sample meeting the diagnostic criteria for anxiety disorders, 1 year following cancer diagnosis. The persistence of high levels of anxiety disorders, may be due to the fact that while approaching medical treatment completion, patients experience fear of cancer recurrence 25 . Another possible explanation may be the complexity that accompanies the adaptation process, of returning to daily activity routine, such as returning to school and resuming social relations with peers, 15 which may provoke anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of high levels of anxiety disorders, may be due to the fact that while approaching medical treatment completion, patients experience fear of cancer recurrence. 25 Another possible explanation may be the complexity that accompanies the adaptation process, of returning to daily activity routine, such as returning to school and resuming social relations with peers, 15 which may provoke anxiety.…”
Section: Discussionmentioning
confidence: 99%